2018
DOI: 10.1002/jez.2233
|View full text |Cite
|
Sign up to set email alerts
|

The effects of endogenous and exogenous catecholamines on hypoxic cardiac performance in red‐bellied piranhas

Abstract: Catecholamines protect the fish heart during hypoxia. However, the humoral adrenergic stress response may only be invoked in extremis. We investigated the hypothesis that endogenous (e.g., neuronal) myocardial catecholamines may also impact cardiac performance during hypoxia in a hypoxia-tolerant tropical fish, the red-bellied piranha (Pygocentrus nattereri). First, we measured endogenous tissue catecholamines and in vitro catecholamine release from piranha myocardium using ultraperformance liquid chromatograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…confound comparisons across species and studies, the ∼50% depression of ventricular F max of normoxia- and hypoxia-acclimated Alaska blackfish with acute hypoxia exposure, plus the recovery of F max to normoxic levels upon reoxygenation, signifies that the Alaska blackfish ventricle is relatively hypoxia-tolerant compared to other water and air-breathing teleosts. By comparison, oxygen limitation reduces myocardial force generation by 90% in rainbow trout ( Gesser, 1977 ), 66% in common carp ( Cyprinus carpio ) ( Gesser, 1977 ) and 50% in the red-bellied piranha ( Joyce et al, 2019 ). In air-breathing fishes, oxygen limitation decreases ventricle contractility by 40–75% in the swamp eel ( Monopterus albus ) ( Iversen et al, 2013 ), Amazonian armored catfish ( Liposarcus pardalis ) ( MacCormack et al, 2003 ) and striped catfish ( Pangasianodon hypophthalmus ) ( Joyce et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…confound comparisons across species and studies, the ∼50% depression of ventricular F max of normoxia- and hypoxia-acclimated Alaska blackfish with acute hypoxia exposure, plus the recovery of F max to normoxic levels upon reoxygenation, signifies that the Alaska blackfish ventricle is relatively hypoxia-tolerant compared to other water and air-breathing teleosts. By comparison, oxygen limitation reduces myocardial force generation by 90% in rainbow trout ( Gesser, 1977 ), 66% in common carp ( Cyprinus carpio ) ( Gesser, 1977 ) and 50% in the red-bellied piranha ( Joyce et al, 2019 ). In air-breathing fishes, oxygen limitation decreases ventricle contractility by 40–75% in the swamp eel ( Monopterus albus ) ( Iversen et al, 2013 ), Amazonian armored catfish ( Liposarcus pardalis ) ( MacCormack et al, 2003 ) and striped catfish ( Pangasianodon hypophthalmus ) ( Joyce et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The following parameters were measured: resting tension, maximal developed force ( F max ; the difference between resting tension and maximal force after electrical stimulation), time-to-peak force ( T PF ) and time-to-half relaxation ( T 0.5R ). Average rate of contraction ( Rate rise ) and average rate of 50% relaxation ( Rate 50% relax ) were calculated by dividing F max by T PF and 0.5 x F max by T 0.5R , respectively ( Galli et al, 2009 ; Joyce et al, 2019 ; Kubly and Stecyk, 2019 ). F max is expressed as mN mm −2 , where mean cross-sectional area was calculated using the strip wet mass, length and an assumed muscle density of 1.06 g cm −3 ( Layland et al, 1995 ).…”
Section: Methodsmentioning
confidence: 99%
“…The full benefit of hypoxic bradycardia may only be appreciated when it is considered in the context of increased parasympathetic and sympathetic stimulation. Adrenergic stimulation, as occurs during hypoxia, steepens the force‐frequency effect in isolated myocardial preparations, ie, the greatest positive inotropic effect of adrenaline is typically achieved at lower heart rates, 182‐184 which is particularly evident during hypoxia 185,186 . In the mammalian (canine) heart, it has been demonstrated that combined sympathetic and parasympathetic stimulation results in a greater increase in cardiac output than even sympathetic activation alone, even when bradycardia prevailed 187 …”
Section: What Is the Benefit Of Hypoxic Bradycardia?mentioning
confidence: 99%
“…Adrenergic stimulation, as occurs during hypoxia, steepens the forcefrequency effect in isolated myocardial preparations, ie, the greatest positive inotropic effect of adrenaline is typically achieved at lower heart rates, [182][183][184] which is particularly evident during hypoxia. 185,186 In the mammalian (canine) heart, it has been demonstrated that combined sympathetic and parasympathetic stimulation results in a greater increase in cardiac output than even sympathetic activation alone, even when bradycardia prevailed. 187 It is striking that the fish and foetal mammalian heart share a variety of structural and functional similarities, from similarities in calcium handling and cardiomyocyte ultrastructure [188][189][190] to the predominance of spongy as opposed to compact myocardium.…”
Section: Accentuated Antagonism In the Mammalian Foetus And Adult Fishmentioning
confidence: 99%